Correction of vibrational broadening in molecular dynamics clusters with the normal mode optimization method - Hudecová, Jana; Hopmann, Kathrin H; Bouř, Petr (The journal of physical chemistry. B, 2012)
Vibrational properties of solutions are frequently simulated with clusters of a solute and a few solvent molecules obtained during molecular dynamics (MD) simulations. The raw cluster geometries, however, often provide unrealistic vibrational band broadening, for both ab initio and empirical force fields. In this work, partial optimization in normal-mode coordinates is used on empirical basis to reduce the broadening. The origin of the error is discussed on a simplified two-dimensional system, which indicates that the problem is caused by the anharmonic MD potential, mode coupling, and neglect of quantum effects. Then the procedure of partial geometry optimization on Raman and Raman optical activity (ROA) spectra is applied and analyzed for the solvated lactamide molecule. Comparison to experiment demonstrates that the normal-mode partial optimization technique with a suitable frequency limit can significantly reduce the broadening error. For lactamide, experimental and simulated vibrational bandwidths are compared; the most realistic theoretical spectra are obtained for partially optimized clusters with the vibrational wavenumber cutoff of about 200 cm(-1).